2014
DOI: 10.1245/s10434-014-4093-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Travel Distance and Time to Radiotherapy on Likelihood of Receiving Mastectomy

Abstract: Background Breast-conserving surgery (BCS) followed by adjuvant radiation therapy (RT) is the standard of care for women with early-stage breast cancer as an alternative to mastectomy. The purpose of this study was to examine the relationship between receipt of mastectomy and travel distance and time to RT facility in New Jersey (NJ). Methods Data were collected from a cohort of 634 NJ women diagnosed with early-stage breast cancer. In patients receiving RT, the precise RT facility was used, whereas in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 15 publications
1
43
0
Order By: Relevance
“…We also found that patients treated with proton therapy traveled significantly longer distances than those treated with photon therapy. 22 The distance to radiation facilities has been shown to affect the selection of treatments, that include radiotherapy (eg, breast conservation therapy and multimodality therapy), [31][32][33][34][35] and our analysis demonstrated that patients treated with proton therapy traveled significantly longer distances than those treated with photon therapy to access the limited number of proton therapy centers in the United States. Our multivariate analysis suggests that socioeconomic factors, including insurance and neighborhood income and education, are significantly associated with differences in the receipt of proton therapy versus photon therapy.…”
Section: Discussionmentioning
confidence: 75%
“…We also found that patients treated with proton therapy traveled significantly longer distances than those treated with photon therapy. 22 The distance to radiation facilities has been shown to affect the selection of treatments, that include radiotherapy (eg, breast conservation therapy and multimodality therapy), [31][32][33][34][35] and our analysis demonstrated that patients treated with proton therapy traveled significantly longer distances than those treated with photon therapy to access the limited number of proton therapy centers in the United States. Our multivariate analysis suggests that socioeconomic factors, including insurance and neighborhood income and education, are significantly associated with differences in the receipt of proton therapy versus photon therapy.…”
Section: Discussionmentioning
confidence: 75%
“…In a previous study of endometrial cancer patients in Arizona, patients with state funded insurance were noted to travel the furthest distance to obtain specialty cancer care [8]. A study of breast cancer patients in New Jersey showed increased travel to be associated with a decreased likelihood of receiving breast conserving surgery and non-private insurance was associated (though not statistically significantly) with increased travel time [22]. Our study confirmed that the elderly and uninsured were traveling the longest distances in order to receive care.…”
Section: Resultsmentioning
confidence: 97%
“…A median car travel time of 28 min may seem long to a suburban health care consumer, but there are many rural counties and states within the United States where this travel time may be in comparison quite short. In a New Jersey study of breast cancer patients an increase in travel time from 12 to 19 min changed rates of treatment acceptance [22]. We were unable to accurately capture utilization of public transportation.…”
Section: Resultsmentioning
confidence: 99%
“…Actual distance to reconstruction was also calculated for those women who underwent reconstruction and was based on the zip code reported on the first claim for reconstruction. Based on thresholds observed in previous literature, 8,9 we then categorized distance to provider into three groups, less than 10 miles, 10 to 20 miles, and greater than or equal to 20 miles.…”
Section: Methodsmentioning
confidence: 99%